SEKOLAH SANTRI MARITIM (SENTRIMAR): EDUKASI LINGKUNGAN MARITIM BERKELANJUTAN BAGI SANTRI SMP UNGGULAN AL-ANWARI - Sakinah, Wazirotus; Arianto, Pratama Yuli; Sumarji, Sumarji; Widityo, Puranggo Ganjar (Jurnal Abdi Insani, 2025)
The Maritime Santri School (SENTRIMAR) is a pesantren-based environmental education model designed to enhance students’ literacy and awareness of sustainable maritime issues. Implemented at Al-Anwari Superior Islamic Junior High School in Banyuwangi, the program leverages its proximity to Santen Island’s coastline as a natural laboratory for experiential learning. Core activities included environmental socialization, mangrove and sea pandanus planting, beach clean-up, and turtle hatchling release, conducted over five months with participatory methods and intensive mentoring. Program evaluation was carried out using pre-test and post-test assessments to measure students’ understanding of maritime environmental concepts. The average pre-test score was 56, which significantly increased to 86 in the post-test. This improvement demonstrates the effectiveness of community-based and hands-on educational approaches in fostering ecological awareness among students. SENTRIMAR not only reinforces pesantren values such as discipline and responsibility but also equips participants with relevant conservation knowledge and skills to address contemporary environmental challenges.